Student Teacher Engagement in Teacher Indirect-Focused Written Corrective Feedback (IFWCF) in a Tertiary EFL Writing Classroom - Kusrin, Kusrin; Supeno (UNIB Press, 2023)
Teacher feedback becomes essential things for student-teachers. It assists them in evaluating learning progress. However, student-teachers’ engagement is under-explored. This present study is objective to showcase Indirect-focused written corrective feedback (IFWCF). This case study focused on investigating the combination of indirect-focused written corrective feedback (IFWCF) simultaneously to the higher education students in Indonesia who engaged affectively, behaviorally, and cognitively in narrative writing class. This study uses the narrative inquiry method. The data were collected from students’ reflective journals and their corrected worksheets as teacher’s feedback and interviews. The results indicate that effectively, students engage IFWCF positively although two participants by birth felt confused and frustrated. Cognitively, students think of making plans to follow up on IFWCF, and behaviorally, they materialize the plans to fix the corrected worksheets. In conclusion, the implementation of IFWCF in writing courses has pedagogical implications for EFL students.